2006
DOI: 10.1001/archpsyc.63.7.731
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Magnetic Resonance Imaging Brain Morphometric Correlates of Brain-Derived Neurotrophic Factor Val66Met Gene Polymorphism in Patients With Schizophrenia and Healthy Volunteers

Abstract: We replicated the association between the BDNF(Met) variant and poor medial temporal lobe-related memory performance. The consonance of our cognitive and brain morphology findings further suggests that the BDNF(Met) variant may have a specific role in conferring visuospatial dysfunction in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
3
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(197 citation statements)
references
References 79 publications
(92 reference statements)
9
181
3
4
Order By: Relevance
“…rs1063843 and cognitive performance Accumulating data indicate that schizophrenia susceptibility genes also influence cognitive function in humans. 45,[71][72][73] Given CAMKK2 as a schizophrenia susceptibility gene X-j Luo et al the important roles of CAMKK2 in hippocampal function and CREB activation, 32,74 we hypothesized that CAMKK2 may also associate with cognitive function in humans. First, previous studies have shown that the activation of CREB is required for longterm memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…rs1063843 and cognitive performance Accumulating data indicate that schizophrenia susceptibility genes also influence cognitive function in humans. 45,[71][72][73] Given CAMKK2 as a schizophrenia susceptibility gene X-j Luo et al the important roles of CAMKK2 in hippocampal function and CREB activation, 32,74 we hypothesized that CAMKK2 may also associate with cognitive function in humans. First, previous studies have shown that the activation of CREB is required for longterm memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the low frequency of the BDNF Met allele (0.18) and the resulting small number of Met/Met homozygotes (n ¼ 3) precluded independent statistical analysis of this genotype group. Thus, analogous to previous DTI studies on this variant (Ho et al, 2006;Kennedy et al, 2009;Montag et al, 2010;Soliman et al, 2010), Val/Met and Met/Met individuals were merged in one group for all analyses. Subject demographics stratified by BDNF genotype are reported in Table 1.…”
Section: Genotypingmentioning
confidence: 99%
“…On the brain structural level, in vivo neuroimaging has provided fairly consistent evidence for gray matter volume reductions in healthy BDNF Met 66 -allele carriers, particularly in limbic areas such as hippocampus and amygdala, at least as inferred from measurements on MRI scans (Ho et al, 2006;Montag et al, 2009;Pezawas et al, 2004). Given that BDNF may target non-neuronal cell types (Cui et al, 2010) and modulates myelinogenesis (Du et al, 2003), it appears plausible that the variant may also impact the microstructure of white matter tracts.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to effects on the hippocampus, studies have also shown decreased volume in the dorsolateral prefrontal cortex, an area associated with planning and higher order cognitive functioning, as well subcortical regions such as the caudate nucleus in carriers of the Met allele (Pezawas et al 2004). Recently it was found that Met allele carriers having smaller temporal and occipital lobar grey matter volumes (Ho et al 2006).…”
Section: Variant Bdnf Met and Behavioural Impairmentsmentioning
confidence: 99%